2018
DOI: 10.3390/urbansci2030065
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Better Understanding of Public Transportation Traffic: A Case Study of the Washington, DC Metro

Abstract: Abstract:The problem of traffic prediction is paramount in a plethora of applications, ranging from individual trip planning to urban planning. Existing work mainly focuses on traffic prediction on road networks. Yet, public transportation contributes a significant portion to overall human mobility and passenger volume. For example, the Washington, DC metro has on average 600,000 passengers on a weekday. In this work, we address the problem of modeling, classifying and predicting such passenger volume in publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…A mixture of principal component analysis (PCA) and k-nearest neighbor (kNN) regression [6]. PCA is used to select the principal components which are input into kNN for prediction.…”
Section: Pca-knnmentioning
confidence: 99%
See 1 more Smart Citation
“…A mixture of principal component analysis (PCA) and k-nearest neighbor (kNN) regression [6]. PCA is used to select the principal components which are input into kNN for prediction.…”
Section: Pca-knnmentioning
confidence: 99%
“…Thus, constructing an effective model to predict the passenger flow volume in a citywide metro network is essential. 2 of 24 During recent decades, many passenger-flow prediction models have been proposed based on statistical and machine learning (ML) algorithms, such as support vector machine (SVM) [2][3][4], Bayesian regression [5], principal component analysis (PCA) [6,7], non-negative matrix factorization (NMF) [8], and artificial neural networks (ANNs) [1,[9][10][11]. However, these conventional methods cannot process raw sample data and require a manual feature engineering procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Using visualization techniques, Sun et al [16] demonstrated the spatial and temporal distributions of passenger flows in a holistic manner, as well as the flow directional imbalances. Zhao et al[17] used statistical-based and unsupervised clustering-based methods to understand the hidden regularities and anomalies of travel patterns and classify passengers in terms of the similarity of their travel patterns.Furthermore, the prediction of passengers' future trajectories [20][21][22][23][24] is also an important issue in transit systems. Yang et al [20] argued that future movements of different types of groups can be predicted with high confidence based on previous records.…”
mentioning
confidence: 99%
“…Yang et al [20] argued that future movements of different types of groups can be predicted with high confidence based on previous records. Truong et al [21] effectively predicted the inand outflow of passengers at a station over time based on the patterns of passenger flow with respect to time and stations. In the study [22], Shanghai was taken as a case study to discuss the location choice of after-work activities, passengers are more likely to choose a station even closer to home in terms of network distance.…”
mentioning
confidence: 99%
See 1 more Smart Citation